Modal Sosial Sebagai Penunjang Eksistensi Pedagang Kaki Lima (PKL): Studi Kasus Pedagang Kaki Lima (PKL) di Alun-alun Kota Kraksaan - Novia Budi Lestari; Dhaehasti Agustina Saputri; Muhammad Furqon (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2023)
The large number of the workforce is unemployed because apart from the lack of employment, there is also a lack of taking advantage of opportunities and a lack of skills. These conditions make them look for alternatives to get income in accordance with the capital they have. Therefore, they decided to become street vendors. The purpose of this research is to find out the problems faced by street vendors and the solutions to these problems in order to encourage the improvement of the merchant's economy and people's welfare. In addition, this study aims to determine social capital that influences the existence of street vendors. This study uses a qualitative method with an ethnographic approach. The results obtained in this study are the need for empowering traders by the government in order to support and enhance sustainable economic development.